PENINGKATAN KETERAMPILAN MENULIS TEKS NARASI MENGGUNAKAN MODEL THINK TALK WRITE DI KELAS IV SD NEGERI 27 SAWAHAN DALAM KOTA PADANG - Desman Agustian; Masniladevi; M Habibi; Salmaini Safitri Syam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low narrative text writing skills of fourth-grade students at SDN 27 Sawahan Dalam, Padang City. Learning was still teacher-centered, teachers did not carry out the three writing stages (pre-writing, drafting, and post-writing), real-life problems close to students were rarely introduced, and students paid little attention to correct spelling, capitalization, punctuation, and word choice. Baseline data showed that only 3 of 11 students reached the Learning Objective Achievement Criteria (KKTP), with more than half of the class failing to reach mastery. This study aimed to describe the lesson planning, the implementation of learning, and the improvement of narrative text writing skills through the Think Talk Write (TTW) model in grade IV of SDN 27 Sawahan Dalam, Padang City. This study used a Classroom Action Research (CAR) design with a mixed qualitative-quantitative approach, following the Kemmis and McTaggart model. The research subjects were 11 fourth-grade students (6 boys and 5 girls). The study was conducted in two cycles: Cycle I with two meetings and Cycle II with one meeting, each consisting of planning, implementation, observation, and reflection stages. Data were collected through observation, tests, and documentation. The results showed that the quality of lesson planning (teaching modules) increased from an average of 90 (very good) in Cycle I to 97.5 (very good) in Cycle II. Teacher activity increased from an average of 85 (good) in Cycle I to 95 (very good) in Cycle II, while student activity increased from an average of 87.5 (good) in Cycle I to 95 (very good) in Cycle II. Students’ narrative writing knowledge scores rose from an average of 70.6 (sufficient) in Cycle I to 87.2 (good) in Cycle II, and their writing process skills rose from an average of 75.6 (sufficient) in Cycle I to 88 (very good) in Cycle II. It can be concluded that the Think Talk Write (TTW) model is effective in improving students’ narrative text writing skills in grade IV of SDN 27 Sawahan Dalam, Padang City.